cis-Selective synthesis of 2,5-disubstituted pyrrolidines - Hussaini, SR; Moloney, M (2004)
A concise approach to cis-2,5-disubstituted pyrrolidines is reported, which relies upon N-tert-butoxycarbonylmethyl substitution in a substrate derived from pyroglutamic acid. The method is especially noteworthy since a significant improvement in the conditions for a key Lawesson's reaction have been established. Regioselective enolate generation and alkylation permits extension of the C-5 side chain. © 2003 Elsevier Ltd. All rights reserved.